Elementary School Teachers’ Perceptions of Digital Technology Based Learning in the 21st Century: Promoting Digital Technology as the Proponent Learning Tools - Miftahul Jannah; Lantip Diat Prasojo; Mohammad Adam Jerusalem (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThis study aims to identify elementary school teachers’ perceptions of digital based learning in the 21st century. Data of this phenomenological qualitative study were collected through interviews with ten teachers in the Special Region of Yogyakarta, and the validity was tested using source triangulation techniques. The data analysis used descriptive data analysis techniques, including data condensation, data display, and drawing conclusion. The results show that teachers consider digital integration in elementary schools to bring positive changes, both in the process and student learning outcomes. It is proven by student responses in the form of increased motivation, activity, enthusiasm, and critical thinking skills. The findings confirm two things. First, the main factor for the success of digital based learning does not depend on the availability of digital equipments, rather in the competence of the teachers (digital skills, creative thinking, and communication skills). Second, teachers in schools with digital technology infrastructure have better performance in implementing digital based learning than those without the infrastructure. This study has implications for the development trends of the competencies of elementary school teachers. Apparently, digital literacy needs special attention in the development of four teacher competencies. Therefore, teachers can keep up with the era and the tendencies of student characteristics.Keywords: teachers’ perception, digital technology, 21st century learning. AbstrakPenelitian ini bertujuan untuk mengidentifikasi persepsi guru sekolah dasar (SD) tentang pembelajaran berbasis digital abad 21. Data dalam penelitian kualitatif jenis fenomenologi ini dikumpulkan melalui wawancara kepada 10 guru di Daerah Istimewa Yogykarta (DIY) dan diuji keabsahannya melalui teknik triangulasi sumber. Analisis data menggunakan teknik analisis data deskriptif, yang meliputi kondensasi data, penampilan data, dan penarikan kesimpulan. Hasil analisis data menunjukkan bahwa guru menganggap integrasi digital di sekolah dasar membawa perubahan positif, baik dalam proses maupun hasil belajar siswa. Ini dibuktikan oleh respon siswa, berupa peningkatan motivasi, aktivitas, antusiasme, dan keterampilan berpikir kritis. Temuan penelitian ini menegaskan dua hal. Pertama, faktor kunci keberhasilan pembelajaran berbasis digital bukan terletak pada ketersediaan peralatan digital, melainkan pada kompetensi guru (keterampilan digital, pemikiran kreatif, dan keterampilan komunikasi). Kedua, guru di sekolah dengan infrastruktur teknologi digital mempunyai kinerja yang lebih baik dalam melaksanakan pembelajaran berbasis digital daripada guru sekolah tanpa infrastruktur teknologi digital. Penelitian ini berimplikasi terhadap tren pengembangan kompetensi guru SD. Literasi digital pada akhirnya perlu mendapatkan perhatian khusus dalam pengembangan empat kompetensi guru, agar guru mampu mengimbangi perkembangan zaman maupun kecenderungan karakteristik siswa. Kata kunci: persepsi guru, teknologi digital, pembelajaran abad 21.